A study to correlate the association of Gender, Age, Physiology (GAP) index and radiological patterns in interstitial lung disease - Aditya Shashi Bhushan; B L Shashibhushan; K Ashwin (Journal of Family Medicine and Primary Care)
Background: Interstitial lung disease (ILD) encompasses a heterogeneous group of disorders characterized by inflammation and fibrosis of lung tissue, leading to impaired gas exchange and respiratory failure. The GAP index, based on gender, age, and pulmonary function, predicts mortality and disease severity in patients with ILD. High-resolution computed tomography (HRCT) is a critical diagnostic tool that provides detailed information on lung morphology and disease extent. This study aims to investigate the relationship between HRCT patterns and the GAP index in patients with ILD, enhancing disease staging and prognostication. Objectives: 1. To identify various radiological patterns in ILD patients using HRCT of the thorax. 2) To correlate these radiological patterns with the GAP index and verify the relationship mentioned above. Materials and Methods: This retrospective observational study analyzed data from 154 patients with ILD treated at Victoria Hospital, Bangalore Medical College and Research Institute, from January 2021 to September 2023. The inclusion criteria included patients aged ≥ 18 years diagnosed with ILD based on the ATS/ERS criteria. Thoracic HRCT was performed using a Philips Ingenuity 128-slice CT scanner, and pulmonary function tests (PFTs) were conducted using a Power cube Diffusion Plus spirometer. The GAP score was calculated, and the HRCT patterns were compared with the GAP stages. Statistical analyses were performed using IBM SPSS Statistics software. Results: The study population had a mean age of 55.5 years, consisting of 68 males and 86 females. Shortness of breath (97.4%) and cough (87.7%) were the most common symptoms. Hypertension (31.2%) and diabetes mellitus (28.6%) were the most common comorbidities observed. The prevalence of definitive UIP sharply increased in stage 3 (58.8%) compared to stage 1 (9.5%) and stage 2 (41.5%), with a highly significant P value (<0.0001). In contrast, NSIP was more common in Stage 1 (39.3%) and decreases in later stages, with a significant P value (0.011). Over half of the patients were in GAP Stage 1 (54.5%), with significant correlations found between advancing GAP stages and an increased prevalence of honeycombing (P = 0.0005) and traction bronchiectasis (P = 0.010). The ground-glass opacity decreased with increasing GAP stage (P = 0.035). Conclusion: This study revealed a significant correlation between particular HRCT patterns and GAP index stages in patients with ILD, highlighting the importance of honeycombing and traction bronchiectasis as indicators of advanced disease. This approach is advantageous in both resource-limited settings, where HRCT availability is limited, and in advanced medical centers, as it can help minimize the need for frequent CT scans.